Structural and ionic conduction study of enhanced bio-polymer electrolytes based carboxymethyl cellulose doped NH4Br - Ahmad Salihin, Samsudin (2017)
The increasing interest in green energy storage materials for electrochemical devices with the development of polymer as electrolytes candidate has attracted great attention recently. It can offer a number of high-value opportunities, provided that lower costs can be obtained besides environmental friendly. Due to this matter, this work presents the discovery on proton conducting bio-polymer electrolyte (BPE) by incorporating various composition of plasticizer namely ethylene carbonate (EC) with biopolymer–salt complexes carboxymethyl cellulose (CMC)–NH4Br.